Produksi Aksesoris Dan Phone Strap HoldnGo Sebagai Upaya Mengatasi Pengangguran - Sagita Aulia Indah Rizkinawati; Maulidyah Indira Hasmarini (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2026)
This research discusses the production of accessories and phone straps called HoldnGo to address unemployment in Indonesia. With the increasing demographic bonus, entrepreneurship becomes an economic solution. The aim is to tackle unemployment and transform beads into high-value products. The method used is descriptive qualitative through observation of the production process, from material selection to marketing. The results show that accessory production can attract consumers and open opportunities for housewives, students, and people with disabilities. This is expected to enhance community welfare through innovation in entrepreneurship.